WEBSITE DESIGN OF INSTITUTE MANAGEMENT TRUSTCO USING Applied Macromedia Flash MX - Sugeng Prasetyo Nugroho (Jurnal Sistem Informasi, 2005)
In this scientific writing, the author makes TRUSTCO LMT website using Macromedia Flash MX. This program created with the aim of facilitate the users to get information about TRUSTCO. This website uses elements of images, text, sound, and animation into a web form that is expected to easily be used by anyone and made it interesting with the music that accompanied this website. In discussing this issue be discussed is the way it started to determine the structure of navigation, making navigation maps, create, design interface, the formation of elements, combining elements, ActionScript programming so it can run. With the push of a button from the options menu the user will immediately get information quickly about TRUSTCO LMT. This program can only run on Windows platform.Bibliography (1960-2005)